2021
DOI: 10.1111/joor.13157
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of swallowing difficulties in older people without neurological disorders: Swallowing profile of older people in the city of Santos, Brazil

Abstract: Several studies report that 40% to 60% of older people have some difficulty chewing and/or swallowing, which can lead to malnutrition, dehydration, weight loss, a lack of eating desire, etc. Identify older adults with swallowing difficulties in the city of Santos, Brazil, among users of the public healthcare system. A cross‐sectional study was conducted with 100 individuals aged 60 to 90 years with no neurological disorders. Patient histories were taken, and stomatognathic evaluations were performed. The Mini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…En segundo lugar, la edad de los pacientes del presente estudio fue significativamente más alta que la de algunos estudios previos (Kwok et al, 2013;Oliveira et al, 2018). Este punto podría ser importante de considerar debido a que existen dificultades en al deglución asociadas a la edad que son altamente prevalentes (Diaz & Lombardi, 2021) y que podrían haber estado subdiagnosticadas pero presentes antes de la intubación. En tercer lugar, se debe considerar que las diferencias de diseño entre estudios también puede influir en las estimaciones reportadas.…”
Section: Modelosunclassified
“…En segundo lugar, la edad de los pacientes del presente estudio fue significativamente más alta que la de algunos estudios previos (Kwok et al, 2013;Oliveira et al, 2018). Este punto podría ser importante de considerar debido a que existen dificultades en al deglución asociadas a la edad que son altamente prevalentes (Diaz & Lombardi, 2021) y que podrían haber estado subdiagnosticadas pero presentes antes de la intubación. En tercer lugar, se debe considerar que las diferencias de diseño entre estudios también puede influir en las estimaciones reportadas.…”
Section: Modelosunclassified
“…Stroke, as a major global cause of death and disability, has always been a key research object in the fields of public health and clinical medicine. [1,2] According to statistics, nearly 15 million people worldwide experience stroke every year, of which about one-third die and another one-third cause long-term disability. Dysphagia belongs to the most common complications after stroke, and according to different studies, approximately 30% to 80% of stroke patients experience dysphagia in the early stages of onset.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that there was a higher prevalence of perception of dysphagia in females (9.4%) and elderly individuals aged 80 years or older (12.6%) in a municipality in southern Rio Grande do Sul (Mello et al, 2021). In the study by Dias and Lombardi (2021), 100 older adults aged 60 to 90 years were evaluated in the city of Santos (Brazil), where 54% of this sample had some difficulty in swallowing, regardless of severity or frequency. According to Bassi et al (2014), the incidence of dysphagia in patients after a stroke is 43 to 50%, even with speech therapy in the first 48 h. Furthermore, as described by Burgos et al (2017), stroke patients are more likely to develop dehydration and malnutrition and have a higher risk of aspiration pneumonia and mortality.…”
Section: Introductionmentioning
confidence: 99%